2021
DOI: 10.4252/wjsc.v13.i7.776
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs from mesenchymal stem/stromal cells: Biology and applications in neuroprotection

Abstract: Mesenchymal stem/stromal cells (MSCs) are extensively studied as cell-therapy agents for neurological diseases. Recent studies consider exosomes secreted by MSCs as important mediators for MSCs’ neuroprotective functions. Exosomes transfer functional molecules including proteins, lipids, metabolites, DNAs, and coding and non-coding RNAs from MSCs to their target cells. Emerging evidence shows that exosomal microRNAs (miRNAs) play a key role in the neuroprotective properties of these exosomes by targeting sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 138 publications
(246 reference statements)
0
13
0
Order By: Relevance
“…Several of the circRNA-associated miRNAs are expressed in the brain, with relatively defined roles in brain development (miR-18a, miR-18b [ 25 , 26 ], miR-30 [ 27 , 28 ], miR-592 [ 29 , 30 ]) or adult brain (miR-18a [ 31 , 32 ], miR-149 [ 33 , 34 , 35 ], miR-30 [ 36 , 37 ], miR-21 [ 28 , 38 ], miR-592 [ 39 ]. Some of these were investigated in the field of dementias and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the circRNA-associated miRNAs are expressed in the brain, with relatively defined roles in brain development (miR-18a, miR-18b [ 25 , 26 ], miR-30 [ 27 , 28 ], miR-592 [ 29 , 30 ]) or adult brain (miR-18a [ 31 , 32 ], miR-149 [ 33 , 34 , 35 ], miR-30 [ 36 , 37 ], miR-21 [ 28 , 38 ], miR-592 [ 39 ]. Some of these were investigated in the field of dementias and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ESCRT-autonomous pathways, including ceramide–interceded mechanisms, have been demonstrated to be implicated in load sorting into EXOs. Additional study is required to discover the particulars of the elective miRNA loading method [ 88 ]. Moreover, RBPs and cell priming (such as hypoxia and inflammatory cytokines) methods can also be used to regulate the miRNA load of EXOs.…”
Section: Mirnas Loading Methods In Msc-exosmentioning
confidence: 99%
“…A relationship matrix analysis investigation demonstrated a weak correlation between the RNA amount of MSC-EXOs and the principal MSCs, showing that miRNAs were electively packed into the EXOs. It has been proposed that RNA-binding proteins (RBPs), including hnRNPA2B1 and hnRNPA1 per se, connect to miRNAs and control Additional study is required to discover the particulars of the elective miRNA loading method [88]. Moreover, RBPs and cell priming (such as hypoxia and inflammatory cytokines) methods can also be used to regulate the miRNA load of EXOs.…”
Section: Mirnas Loading Methods In Msc-exosmentioning
confidence: 99%
“…Studies have shown that miR-137 targeted OXR1 and negatively regulated its expression, and inhibiting miR-137 or up-regulating OXR1 can promote the vitality of neurons in PD models and minimize apoptosis, accompanied by a drop in MDA content and ROS levels and an increase in SOD levels ( Jiang et al, 2019 ). Exosomes derived from Mesenchymal Stem Cells/Somatic Cells (MSC) can transport miRNAs to neuronal cells and are critical in immunological modulation, neurite remodeling, neurogenesis, and axonal growth and CNS recovery ( Vilaca-Faria et al, 2019 ; Nasirishargh et al, 2021 ). Jiang et al injected serum-derived exosomes into PD mice, and the loss of function of miR-137 antagomir demonstrated that miR-137 down-regulation could minimize PD’s oxidative stress damage by up-regulating OXR1, reduce pole-climbing time, and increasing traction test score ( Jiang et al, 2019 ).…”
Section: The Pathogenic Effect Of Exosomal Non-coding Rna On Parkinso...mentioning
confidence: 99%